Antibodies Against Pseudomonas aeruginosa Alkaline Protease Directly Enhance Disruption of Neutrophil Extracellular Traps Mediated by This Enzyme - Jing, Chendi; Liu, Chenghua; Liu, Yu; Feng, Ruli; Cao, Run; Guan, Zhangchun; Xuan, Bo; Gao, Yaping; Wang, Qi; Yang, Nana; Ma, Yuanfang; Lan, Lefu; et al. (Frontiers in Immunology, 2021)
Extracellular traps released by neutrophils (NETs) are essential for the clearance of Pseudomonas aeruginosa. Alkaline protease (AprA) secreted by P. aeruginosa negatively correlates with clinical improvement. Moreover, anti-AprA in patients with cystic fibrosis (CF) can help identify patients with aggressive forms of chronic infection. However, the mechanism underlying the clinical outcomes remains unclear. We demonstrated that aprA deficiency in P. aeruginosa decreased the bacterial burden and reduced lung infection. AprA degraded NET components in vitro and in vivo but did not affect NET formation. Importantly, antibodies induced by AprA acted as an agonist and directly enhanced the degrading activities of AprA. Moreover, antisera from patients with P. aeruginosa infection exhibited antibody-dependent enhancement (ADE) similar to that of the antibodies we prepared. Our further investigations showed that the interaction between AprA and the specific antibodies might make the enzyme active sites better exposed, and subsequently enhance the recognition of substrates and accelerate the degradation. Our findings revealed that AprA secreted by P. aeruginosa may aggravate infection by destroying formed NETs, an effect that was further enhanced by its antibodies.